THE ROLE AND LINGUOPOETIC CHARACTERISTICS OF EXPLICIT MEANING IN ORATORY - Orazov Adilbay Orinbayevich (The Conference Hub, 2025)
Explicit meaning (open, direct meaning) plays an important role in studying the linguopoetic features of oratory. Explicit meaning is the clear and accurate conveyance of the main idea of speech through linguistic means. This method aims to directly influence the listener's consciousness; therefore, in folklore works, especially in oratory and proverbs, explicitness occupies a dominant position.